SIDE EFFECTS OF TEMOZOLOMIDE CHEMOTHERAPY IN GLIOMA AND MANAGEMENT - Sukmala Ratih, Dwita; Rahmawati, Dessika (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2025)
Glioma is the most common type of primary brain tumor and is characterized by aggressive growth, angiogenesis, and invasion. Current therapies for malignant glioma have limited efficacy, necessitating new treatment strategies.1 Every year, approximately 100,000 people worldwide are diagnosed with glioma. These tumors are categorized based on tumor histology and molecular alterations. Survival rates depend on tumor subtype, age, and gender.4 Glioblastoma is a specific type of glioma and is the most aggressive and malignant form. It is often linked to unfavorable outcomes and has few available treatment choices.2 Temozolomide is a drug used in the treatment of glioma, which is the most common primary malignant tumor of the Central Nervous System (CNS). It is a chemotherapy drug that is often used in combination with radiation therapy to treat gliomas. It works by damaging the DNA in cancer cells, which prevents them from dividing and growing. This agent may help slow or stop tumor growth. TMZ is often used in combination. Close monitoring of patients receiving bevacizumab or temozolomide is required to manage potential side effects resulting from the use of these regimens.3